Sustainable responsible conduct beyond the boundaries of compliance: Lessons from Italian listed food and beverage companies. Issue 5 (3rd June 2019) - Fiandrino, Simona; Busso, Donatella; Vrontis, Demetris
Abstract : Purpose: The purpose of this paper is to investigate whether Italian listed companies within the food and beverage (F&B) industry adopt sustainable responsible conduct beyond the boundaries of compliance and which industry-specific matters the companies address as core to their business within a regulatory setting of sustainability disclosure. Design/methodology/approach: This study develops a multiple case study of the five Italian listed companies in the F&B industry and employs a content analysis on their sustainability reports. Findings: This study reveals a policies–practices decoupling along with a means–ends decoupling that jeopardises the commitment to sustainability. The results show a reasonable level of compliance, but companies are at an early stage of coherent and practical application. Practical implications: This study offers practical avenues for companies, regulators and policy makers. Companies in the F&B industry are guided towards the learning process to shape sustainable, responsible practices at the core of their business, as this study provides a replicable assessment of F&B sustainability issues. Regulators and policy makers are called to monitor the concrete implementation of sustainability issues and improve the understanding of the sustainability agenda to overcome the misalignments that companies are currently facing. Originality/value: This study provides fertile ground for assessing the degree of maturity in favour of sustainable responsible conduct within the F&B industry and shows the obstacles to this commitment in the mandatory setting of sustainability disclosure.